ANALISIS EVALUASI KESESUAIAN LAHAN PERUMAHAN DI KOTA MANADO DENGAN MENGGUNAKAN GEOGRAPHIC INFORMATION SYSTEM DAN MULTIPLE CRITERIA DECISION MAKING - Solang, Maxi W; Mandagi, R J; Lumenon, Shirly S (Sam Ratulangi University, 2017)
Manado city is as the capital of North Sulawesi Province which has high dynamics and urban activity so that spur population growth which more solid. Along with the rapid growth of the population, the supply of land as a source of housing construction becomes the need of each individual becomes increasingly limited. The transfer of land use in urban areas to meet the increasing need for housing for the community should always consider the development site aspect in accordance with the spatial plan, land suitability based on physical parameters, and policies of local stakeholders to create a balanced environment and provision of efficient facilities and infrastructure. Housing development planning can be done by using spatial analysis method to produce the location of determination in accordance with the spatial plan and land suitability, also using MCDM method to get priority location determination of development of settlement area. The purpose of this study is to identify suitable housing areas in Manado City, to analyze the evaluation of land suitability of housing and model of location determination and land area through MCDM method by involving geographical spatial element, to determine alternative land management strategy for housing in Manado City.The analysis process begins with the processing of GIS datasets (vector, raster) and non spatial data. After that use weighting technique and analyzed by weighted overlay method. To produce an integrated GIS analysis then data processing is done on ArcGIS 10.4.1 software. The process of perception analysis to obtain the best management strategy in the development of residential land in Manado City by processing the questionnaire data on Expert Choice 11 software.The result of the analysis resulted in the sub-district having land for the very suitable housing (S1) located in Kecamatan Mapanget for 4,406.43 Ha, then the sub-district with the Classification Suitable (S2) located in District Bunaken 1,879.02 Ha, Subdistrict with classification of Marginal Appropriate (S3) is located in the Bunaken Islands Sub-district of 1,310.87 Ha, and the Kecamatan with the Unsuitable (N) classification is located in the Bunaken Islands District of 106.31 Ha.The best alternative management strategy in the development of residential land in Manado City is; continuing policies in accordance with the spatial plan of Manado city, prioritizing housing, prioritizing housing if appropriate areas, prioritizing housing with sustainable development. The result of the weighting is obtained by consistency value of 0.08 with highest alternative that is giving priority to housing with value 0,342Â Â Â Keywords: Evaluation of Land Suitability, Housing, GIS, MCDM.